2023
DOI: 10.1108/lhtn-07-2023-0126
|View full text |Cite
|
Sign up to set email alerts
|

Implementing artificial intelligence in library services: a review of current prospects and challenges of developing countries

Abstract: Purpose Artificial intelligence (AI) is one of today’s rising technologies. AI is a commonly used technology in library services that have the potential to revolutionise the best offerings in the information age. With AI in libraries, users can explore the world of knowledge like never before with smart recommendations tailored to their needs. Overall, AI can enhance the library experience of both the users and library professionals with innovation and smart decisions. Hence, there is no doubt that AI and libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Hussain (2023) highlights in his study that most of the librarians in developing countries are still unaware regarding the potential deployment of Artificial Intelligence in the libraries. In this context, Barsha and Munshi (2023) suggested that “educational institutions and libraries should offer training programs and workshops to enhance the skills of library professionals in AI technologies” (p. 9). Although, integrating AI and other emerging technologies in library services are the future of academic library system.…”
Section: Embedded Librarianshipmentioning
confidence: 99%
“…Hussain (2023) highlights in his study that most of the librarians in developing countries are still unaware regarding the potential deployment of Artificial Intelligence in the libraries. In this context, Barsha and Munshi (2023) suggested that “educational institutions and libraries should offer training programs and workshops to enhance the skills of library professionals in AI technologies” (p. 9). Although, integrating AI and other emerging technologies in library services are the future of academic library system.…”
Section: Embedded Librarianshipmentioning
confidence: 99%
“…However, implementing AI in predictive marketing in developing countries also presents unique challenges (Wright and Schultz, 2018). Infrastructure limitations, budget constraints and varying levels of digital literacy can influence the adoption and impact of AI in these regions (Barsha and Munshi, 2023). In addition, while universal, ethical considerations may have different contextual implications in developing nations, as discussed in the study by World Health Organizaion (WHO) (2021) on AI ethics in a South Asian context.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…These libraries' fundamental objective is to provide users with relevant resources needed to generate knowledge (Atuase and Filson, 2024). However, owing to financial constraints on the part of the universities (Barsha and Munshi, 2024; Intahchomphoo et al., 2016; Crawford, 2015), most libraries cannot provide the requisite number of recommended textbooks that match the ratio of library users. This has undoubtedly led to inefficiency in library service (Baada et al., 2020) and struggle over the few resources.…”
Section: Introductionmentioning
confidence: 99%